An analytical method to predict electromigration-induced finger-shaped void growth in SnAgCu solder interconnect. (15th January 2015) - Yao, Yao; Wang, Yuexing; Keer, Leon M.; Fine, Morris E.
Abstract : An analytical solution to predict electromigration-induced finger-shaped void growth in SnAgCu solder interconnect is developed based on mass diffusion theory. A quantitative nonlinear relation between the void propagation velocity and the shape evolution parameter is obtained. It is found that a circular void will grow at the lowest velocity, but as it collapses to a finger-shaped void it will grow at a faster velocity that is inversely proportional to the width. The void growth velocity predicted is consistent with the experimental observation.